Thermomechanical modeling of halloysite nanotube-filled shape memory polymer nanocomposites. Issue 14 (18th July 2019) - Bouaziz, Rami; Prashantha, Kalappa; Roger, Frédéric
ABSTRACT: In this paper, we propose to improve static and dynamic mechanical performance of thermoplastic polyurethane (TPU) shape memory polymer by the addition of halloysite nanotubes (HNTs). In addition, we propose a finite element simulation of neat TPU and its nanocomposites. HNT/TPU nanocomposites as shape memory polymers with different weight percentages of nanotubes contents were prepared by melt extrusion with thermoplastic polyurethane. This process induced a homogeneous distribution and a good dispersion of nanotubes throughout the TPU matrix. Mechanical tests in tension demonstrated that strength and modulus of the nanocomposites significantly increase with addition of halloysites without significant loss of ductility. Moreover, cyclic shape memory tests under large strain showed that shape memory properties, mainly the recovery speed, were also enhanced. Using a thermo-visco-hyperelastic model for shape memory polymers, we have investigated the effect of nanotubes addition on the mechanical parameters. This model showed a good prediction of the mechanical behavior during shape memory tests.